Structure–activity relationship of cyclic pentapeptide malformins as fibrinolysis enhancers. Issue 21 (1st November 2016) - Koizumi, Yukio; Nagai, Kenichiro; Hasumi, Keiji; Kuba, Keiji; Sugiyama, Toshihiro
Graphical abstract: Abstract: The formation of blood clots in blood vessels causes severe ischemic diseases such as cerebral infarction and myocardial infarction. While searching for microbial products that increase fibrinolytic activity using an in vitro fibrin degradation assay, we found malformin A1, a disulfide form of cyclo (–d -Cys-d -Cys-l -Val-d -Leu-l -Ile–), as an active compound. In this study, we synthesized malformin derivatives using a solid-phase peptide synthesis method and evaluated their fibrinolytic activity and cytotoxicity. Reduction of the disulfide bond and linearization of the cyclic peptide frame decreased the pro-fibrinolytic activity. Substitution of a branched-chain amino acid with lysine resulted in loss of activity. However, protection of the amino group in the lysine derivatives by the tert -butoxycarbonyl (Boc) group rescued the inactivity. Furthermore, the phenylalanine derivatives also exhibited a similar pro-fibrinolytic effect compared to malformin A1. These results suggest that the disulfide bond, the cyclic peptide frame, and the bulky hydrophobic side chains play a crucial role in the pro-fibrinolytic activity of malformin. The effective dose of the active derivatives for the in vitro fibrin degradation showed similar ranges (1–5 μM), while the order of cytotoxic potency for the active derivatives was as follows: Phe-derivatives > BocLys-derivatives > malformin A1 > reduced form. These results showed no correlation between pro-fibrinolytic activity and cytotoxicity, suggesting the possibility of the synthesis for non-toxic malformin derivatives possessing the activity.